2009
DOI: 10.1177/0363546509339009
|View full text |Cite
|
Sign up to set email alerts
|

Golf After Total Knee Arthroplasty

Abstract: In this population of golfers, total knee arthroplasty reliably relieved pain that had been previously experienced while golfing, and increased or maintained this group's enjoyment of playing golf. However, 86% of these patients reported using a cart while golfing. Further patient education is needed regarding the potential health benefits of walking during golf after total knee arthroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 15 publications
2
25
1
1
Order By: Relevance
“…6,8,21 In a study by Huch et al, 21 the majority of patients cited “precaution” as the reason for their decreased postoperative athletic activity, which is most likely influenced by surgeons counseling patients to protect the life span of their prostheses. In contrast, there have been studies in the literature reporting that patients may actually increase their sports involvement after surgery 22,56 and that there may be little to no adverse effects of high activity on TKA or THA. 41 In light of these contradictory findings and increasing patient desires to engage in a highly active lifestyle, many surgeons now promote a more liberal level of athletic activity after TJA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,8,21 In a study by Huch et al, 21 the majority of patients cited “precaution” as the reason for their decreased postoperative athletic activity, which is most likely influenced by surgeons counseling patients to protect the life span of their prostheses. In contrast, there have been studies in the literature reporting that patients may actually increase their sports involvement after surgery 22,56 and that there may be little to no adverse effects of high activity on TKA or THA. 41 In light of these contradictory findings and increasing patient desires to engage in a highly active lifestyle, many surgeons now promote a more liberal level of athletic activity after TJA.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, more than 500 000 total joints are implanted yearly 27 with approximately 300 000 knee replacements performed each year in the United States alone. 22 Although pain relief has historically been the primary indication for TJA, more and more individuals are now seeking TJA to maintain an active lifestyle; specifically, patients are seeking surgical interventions to restore their ability to participate in various athletics. 54 Many patients have embraced higher expectations for an active lifestyle, incorporating athletic activities as part of their functional goals following surgery.…”
mentioning
confidence: 99%
“…Of these, 3 studies 26,48,49 only included patients who were active in athletics. The studies reported a wide range of patients who returned to recreational activities (34%-100%; Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…4 Pain in the knee was reported during activity in 16% in 1 study 24 and in 17% in another. 26 One investigation 23 reported that 26% of patients had pain in their knee and 26% had a feeling of instability during participation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation